2019
DOI: 10.21272/bel.3(4).6-14.2019
|View full text |Cite
|
Sign up to set email alerts
|

History of Childhood Oppression, Inter-Temporal Resentment and Compliance with Codes of Harassment at the Workplace: An Offender’s Perspective

Abstract: This study tends to identify intents and inclinations that explain low/ high compliance with the codes of provocation/harassment, at the workplace. Despite the reason and the fact that most literature on the subject takes into account the perspective of victims of harassment at workplace, this study prefers to take cross-sectional basis of the offender’s perspective. Studies on matters of harassment are generally prone to potential syndromes such as ‘accuse the victim’ and deliberation by state institutions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…The basic statistical equation for logit model regression that was previously used in scientific research in different fields of study (Vohra & Pavleen, 2015;Kovacova & Kliestik, 2017;Václav & Hampel, 2017;Waqas & Rohani, 2018;Arroyave, 2018;Dawood et al, 2019;Saima, 2019;Akhter & Butt, 2019) is as follows:…”
Section: Research Model and Methodologymentioning
confidence: 99%
“…The basic statistical equation for logit model regression that was previously used in scientific research in different fields of study (Vohra & Pavleen, 2015;Kovacova & Kliestik, 2017;Václav & Hampel, 2017;Waqas & Rohani, 2018;Arroyave, 2018;Dawood et al, 2019;Saima, 2019;Akhter & Butt, 2019) is as follows:…”
Section: Research Model and Methodologymentioning
confidence: 99%
“…Для построения модели прогнозирования проявлений системного банковского кризиса среди методов статистического анализа был выбран метод логистической регрессии (logit-модель) -модель бинарного выбора на базе логистической функции. Выбранный научно-методический инструментарий позволяет предсказывать вероятность возникновения некоторого события (в данном случае банковского кризиса) по значениям множества признаков [36][37][38][39][40][41][42][43][44][45].…”
Section: бинарное моделирование: методология исследованийunclassified
“…Some violent acts can be caused by illness or mental health problems, but most of them are caused by the intentional actions of criminals through stereotypes, aggressive behavior, and misunderstandings (Mujtaba et al, 2020). When the effects of drug abuse were observed, it was shown that most persons under observation were tormented from emotional imbalance (Akhter and Humna, 2019).…”
mentioning
confidence: 99%